Repurposing of Oxicam Derivatives to Inhibit NDM-1: Molecular Docking and Molecular Dynamic Simulation Studies - Pshtiwan Gharib Ali; Twana Mohsin Salih (College of Pharmacy / Mustansiriyah University, 2024)
The New Delhi Metallo-β-lactamase-1 (NDM-1) causes hydrolysis of broad spectrum β-lactam antibiotics, such as carbapenems, resulting in the development of antimicrobial resistance. Still, there are not any approved NDM-1 inhibitors, globally. Therefore, repositioning approved medicines as NDM-1 inhibitors to combine with carbapenems may be a crucial strategy to combat resistant pathogens. This study repurposes. Oxicam derivatives as inhibitors of bacterial NDM-1. The two-dimensional structures were obtained from the PubChem database. Twenty derivatives of oxicam were assessed computationally to realize their NDM-1 inhibition capability.  To identify potential inhibitors of the NDM-1 target protein, a molecular docking protocol was used. In addition, drug-likeness and pharmacokinetic properties were predicted for the designed molecules. Three compounds with the most negative ΔGbinding results were chosen for additional study using molecular dynamic (MD) simulations. The compounds M010, M013, and M016 possessed a significantly more negative binding free energy than the positive control and other designed molecules, had stable MD simulations (Root-mean-square deviation < 0.5 Å), passed Lipinski's rule of five, and possessed favourable physicochemical and pharmacokinetic properties. The findings can inform In vitro studies of the promising compounds.